Spain : Financial Sector Reform: Second Progress Report. (IMF Staff Country Reports; Country Report ;, 2013)
This article is a report of Spain's progress in financial sector reforms. The key reforms in the financial sector have been either adopted or designed. The economy has risks at times as it takes up the challenges of correcting pre-crisis imbalances. The economy may face decline, but financial markets have significantly improved. Financing from banks is a major source of finance for households and firms. Exports contribute to the increasing economy in spite of global competition. The Executive Board welcomes this development of Spain's financial sector.